Prevalence and Correlates of Vitamin D Inadequacy in a Sample of Iraqi People - Ismael Hasan Jawad1 , Hasan ALwan Baiee2 , Issam Salim Ismail3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Vitamin D had been identified as a common metabolic/endocrine abnormality. Middle Eastcountries had a very high rate of vitamin D inadequacy, vitamin D deficiency was associated with noncommunicable and infectious diseases.Objective : To identify the prevalence of Vitamin D level and its correlates among Iraqi people in Al-Hillacity-Babylon provinceMethods :. A cross?sectional study was conducted on a convenient sample of individuals from all age groupsand both genders who attended eight primary health care centers and individuals in Al?Hilla city, the study period was started from May through October , 2019. A pretested questionnaire wasused for data collection , the questionnaire included information regarding socio demographic characteristicsof participants and their history of chronic diseases. The following measurements were done: level of serumvitamin D , blood pressure, blood sugar , body weight and weight and the serum of vitamin D .Results: The sample included 188 participants their mean age was 64.8 ± 17.25 years.The female to maleratio 1.7:1, More than half of participants (56%) resident in urban areas . Vitamin D mean level was (20.7ng/mL ± 14.9 SD). The vast majority (80%) of the sample have vitamin D inadequacy in which (66% havedeficiency and 14% have insufficiency), while 37 (20%) of the sample have vitamin D adequacy.A significant inverse relationship between vitamin D serum level and hypertension, type two diabetesmellitus, increase body weight.Conclusion: there was a high prevalence of vitamin D inadequacy among Iraqi people mainly in females,a significant association between low vitamin D level and hypertension, type two diabetes mellitus, andobesity.